1983
DOI: 10.1099/00221287-129-7-2199
|View full text |Cite
|
Sign up to set email alerts
|

The Serological Properties of the Cell Surface Proteins of Vibrio cholerae

Abstract: The serological properties of cell surface proteins of Vibrio cholerae belonging to both the biotypes (classical and El Tor) and the serotypes (Ogawa and Inaba) were investigated. Proteins were isolated by extracting V. cholerae with EDTA in the presence of sodium chloride. The surface localization of these proteins was confirmed with (a) radioiodinated protein A as an immunoprobe and (b) antiserum absorption studies with whole bacteria. There were similarities among the polypeptides of cell surface proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…As reported by others (e.g., Kabir, 1983;Sears et al, 1984), SDS-PAGE separation and immunoblotting indicated that there were physico-chemical and serological similarities among the major monomeric sub-units of OMPs prepared from strains of the common serotypes of V. cholerae. Furthermore, it is obvious that LPS association with a number of these proteins precludes direct assessment of their protective capacity.…”
Section: 'Discussionsupporting
confidence: 53%
“…As reported by others (e.g., Kabir, 1983;Sears et al, 1984), SDS-PAGE separation and immunoblotting indicated that there were physico-chemical and serological similarities among the major monomeric sub-units of OMPs prepared from strains of the common serotypes of V. cholerae. Furthermore, it is obvious that LPS association with a number of these proteins precludes direct assessment of their protective capacity.…”
Section: 'Discussionsupporting
confidence: 53%
“…The sera were treated as previously described (17) to remove antibodies to the LPS. Briefly, 1 ml of serum was mixed with 5 mg of LPS isolated from A. pleuropneumoniae and 0.5% sodium azide.…”
Section: Methodsmentioning
confidence: 99%
“…Cell-surface proteins were extracted from V. cholerae cells with EDTA-NaCl as described by Kabir (1983a), Briefly, 2 g (wet weight) of V. cholerae cells was washed twice with cold EDTA-NaCl(5 ml; 0.12 M EDTA, 0.77 M NaCl, pH 7-2). The combined extracts obtained after centrifugation (20 000 9, 30 min) were concentrated by negative pressure dialysis against PBS and again centrifuged for 15 min.…”
Section: Extraction Of Cell-surface Proteins Of V Choleraementioning
confidence: 99%
“…Its cells possess somatic components that include lipopolysaccharides (LPS) and surface proteins that are immunogenic in man and in experimental animals (Majumdar et al, 1981 ;Kabir, 1982Kabir, , 1983a. V .…”
Section: Introductionmentioning
confidence: 99%